ASSOCIATION OF THE ACSL5 GENE G.33185918G>A AND G.33186348C>T MUTATIONS WITH CARCASS AND MEAT QUALITY TRAITS OF CHINESE SIMMENTAL-CROSS STEERS - H. Xiao; Z. Zhao; X. Fang; H. Yu; X. Long; P. Jiang; R. Yang (Journal of Animal and Plant Sciences, 2016)
Acyl coenzyme A long-chain 5 synthetase (ACSL5), a member of the ACSL family, plays a key role in fatty acid beta-oxidation and fat synthesis in mammals. In this study, two SNPs g.33185918G>A and g.33186348C>T in the 5’ flanking sequence of the bovine ACSL5 gene were identified by PCR-RFLP. Thus, we aimed to evaluate the association between the two SNPs and meat quality traits, in addition to the carcass quality of Chinese Simmental-cross steers. The two SNPs were genotyped, and 36 carcass and meat quality traits were measured in a population of 354 individuals. Statistical analysis revealed that the two SNPs were significantly associated with carcass and meat quality traits. g.33185918G>A was very significantly (p<0.01) associated with the weight of the omasum and the pH of beef. For g.33186348C>T, the weight of the liver, hind hooves, kidney, and testis and the fat coverage rate of the carcass were very significantly associated (p<0.01). The present work indicated that polymorphisms in ACSL5 might be important genetic factors affecting meat quality and carcass yield in Chinese Simmental-cross steers. Moreover, such polymorphisms may serve as practical markers for carcass and meat quality traits in future marker-assisted selection (MAS) programs in beef cattle breeding and production.
Keywords: ACSL5; Chinese Simmental cattle; SNPs; Meat quality trait; MAS